Pengaruh PDRB, Partisipasi Tenaga Kerja, dan Tingkat Pendidikan terhadap Ketimpangan Pendapatan di Indonesia Bagian Barat Tahun 2015–2025 dalam Perspektif Ekonomi Islam - M.Readdy Darussalam; Supaijo Supaijo; Alief Rakhman Setyanto (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2026)
This investigation seeks to ascertain the extent of the influence of GRDP, labor force participation, also education levels on income inequality in Western Indonesia from 2015 to 2025, using the perspective of Islamic economics as the primary analytical framework. The investigation's data came from Indonesian government reports published by the Central Statistics Agency (BPS), They were subsequently analyzed quantitatively using the Panel Data Regression technique with three requirements, including the Common Effect Model (CEM) test, Fixed Effects Model (FEM) test, and Random Effects Model (REM) test; the best model was selected using the Chou test, the Harsman test, and the Lagrange Multiplier (LM) test. Additionally, a Classical Assumptions test, specifically a Normality test, was conducted. The F-test, partial t-test, and coefficient of determination (R²) test were then used for hypothesis testing. Considering the test findings, the model selected in this investigation is REM. The investigation's findings show the GRDP variable significantly also favorably affects income inequality, whereas Income inequalityis not significantly impacted by labor force participation also educational level. From the perspective of Islamic economics, economic development focuses not just on economic growth, but also on the creation of justice and the equitable distribution of welfare among the people. Islam emphasizes the importance of fair income distribution through the principle of social justice also Islamic economic instruments, like sadaqah, zakat, and infaq, so that welfare can be enjoyed equally and excessive inequality does not arise in society.